Cu-Ni bimetal integrated TiO2 thin film for enhanced solar hydrogen generation - Tudu, Bijoy; Nalajala, Naresh; Saikia, Pranjal; Gopinath, Chinnakonda S. (Solar RRL, 2020)
A series of non-noble Cu-Ni bimetallic catalysts is prepared with different molar proportions of metals. Of these bimetallic catalysts, 1 wt% is subsequently integrated with titania P25. The catalysts are evaluated for solar hydrogen generation under 1 sun condition in both the powder and thin film forms. All the photocatalysts in the thin film exhibit an 8-24 times higher hydrogen yield (HY) compared with the corresponding particulate counterpart. The highest HY (41.7 mmol h(-1) g(-1)) is demonstrated for the photocatalyst Cu-Ni/TiO2 (CNT; 1:1 = Cu:Ni) in the thin film form, which is 24 times higher than that with its powder counterpart (1.75 mmol h(-1) g(-1)) and exceeds the performance of other Cu-Ni/TiO2 compositions. This enhanced activity in the thin film can be ascribed to improved absorption of visible light and an effective separation of photogenerated charge carriers at the interface of Cu-Ni/TiO2 leading to better charge carrier utilization.
Keywords: bimetals; energy conversion; Hydrogen; Photocatalysis; solar energy